The impact of parental socioeconomic status and parental involvement on young children’s music lesson / Law Yi Xian - Law , Yi Xian (2018)
The parents’ socioeconomic status has a direct link to the parents’ choice of involvement and their children’s engagement in activities related to musical learning (Margiotta, 2011). However, insufficient evidence exists regarding the relationship between parental socioeconomic status and the choice of parental involvement, children’s engagement in musical learning activities. The purpose of this study sought to investigate the impact of parental socioeconomic status on parental involvement in their children’s private instrumental learning and their children’s engagement in activities that are associated to music learning. It also study the value of parental involvement in their children’s music learning from parents’ perspective. 80 parents with their children (5 to 12 years old) enrolled in one-to-one instrumental music classes throughout the Klang Valley region were participated in this study. The main tools for data collection were questionnaire for parents. The quantitative data from the questionnaires was analyzed using descriptive statistics. The results suggest that the socioeconomic status of the parents does make a positive impact in their involvement, their children’s engagement in music learning activities and also their perspective towards the value of parental involvement. Parents with higher socioeconomic status have higher involvement in their children’s music education and have positive thinking on the value of parental involvement. Besides, children from upper class family engage more in music learning activities. As this study suggests that the parental socioeconomic status have a significant impact on their involvement, perspective and the children’s engagement, instrumental teachers should pay more attention on the children background in order to provide appropriate guidance and support based on the needs of each students and their parents. A more regular communication and interaction between teacher, student and parents about challenges they encounter, their expectations and progression contribute to the growth of the children’s music learning.